Pengaruh Teknologi, Pengelolaan Arsip, Sarana Prasarana, dan Pelatihan terhadap Kinerja Pegawai Badan Pengelolaan Keuangan dan Aset Daerah Kota Batam - Asridianti Asridianti; Dewi Permata Sari; Septa Diana Nabella (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the influence of technology utilization, records management, infrastructure, and training on employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Batam City. A quantitative approach with an associative design was employed to identify relationships between variables and measure their effects. The study involved 89 employees as respondents using a saturated sampling method to ensure all members of the population were included. Data were collected through structured questionnaires and analyzed using multiple linear regression along with F-test and t-test to assess both simultaneous and partial effects. The findings reveal that all independent variables simultaneously have a significant impact on employee performance, while individually technology, records management, infrastructure, and training also demonstrate significant positive effects. These results indicate that the effective use of digital systems, well-organized archival practices, adequate and supportive facilities, and continuous training programs play a crucial role in enhancing employee performance and productivity, as well as improving efficiency, accuracy, and overall organizational effectiveness. The study suggests that organizations should strengthen technological implementation, improve document management systems, provide sufficient work facilities, and conduct sustainable training programs to achieve optimal and long-term organizational outcomes.